A bistable energy harvester with low base-acceleration and high root mean square output for train bogies: theoretical modeling and experimental validation. (1st March 2023) - Tu, Dilong; Zhang, Yuan; Zhu, Lei; Qin, Yong; Du, Yanping; Liu, Mengzhou; Ding, Ao
Abstract: Energy harvesting provides potential power solutions for distributed sensors in rail transportation condition monitoring. However, reported harvesters have low efficiency and a narrow working bandwidth for rail transportation condition monitoring scenarios. An energy harvester is developed in this paper that has a higher energy output efficiency and a wider working bandwidth. The harvester is suitable for train monitoring scenarios. The key novelty lies in the combination of a spherical moving magnet and a cylindrical moving magnet to give a spherical–cylindrical coupled moving magnet, which not only maintains the advantage of low friction but also improves energy conversion efficiency. Furthermore, analytical models are established to describe the dynamics of the harvester with different moving magnets (spherical, cylindrical, spherical–cylindrical coupled), and a theoretical framework is established to guide the design. The theoretical model is validated by developed prototypes and experimental results. The working bandwidth of the energy harvester with a spherical–cylindrical coupled moving magnet is 9.5–45.1 Hz at 2 g and the output power reaches 18.2 mW at 40 Hz and 1200 Ω load. Compared with traditional energy harvesters with cylindrical and spherical moving magnets, the base excitation is lower and the normalized output power is higher. Thus, this energy harvester is more suitable for train monitoring scenarios.